Visual functioning and cerebral visual impairment in children with infantile spasms - West syndrome - Vučinić Vesna; Martać Valentina; Cerovac Nataša; Stamenković Miroslav (Srpski Arhiv za Celokupno Lekarstvo)
Cerebral visual impairment (CVI) is the most common cause of visual impairment in children in both developed and developing countries, making it a relevant research topic on the functional status of neuro-risk children in recent decades. The multifactorial nature of West syndrome (WS) and the variability in visual functions and functioning hinder the timely diagnosis of this type of visual impairment. The atypical ways of following stimuli, establishing and maintaining visual contact, and sustaining visual attention are the first indicators of deviations in visual behavior that may suggest neuro-risk. Changes in visual behavior may manifest as alterations in the quality or absence of visual responsiveness, deficits in various visual functions and oculomotor skills, often associated with atypical findings in visual evoked potentials. Cortically mediated visual functions, such as visual acuity, visual field, contrast sensitivity, and oculomotor skills, are also at risk in children with infantile spasms and WS. In addition to basic visual functions, visuo-perceptual and visuo-motor skills are significantly affected, which is manifested in everyday behavior and motivation to observe. The degree and manifestations of CVI in children with infantile spasms depend on numerous factors. Multidisciplinary diagnostic procedures that determine whether cerebral visual impairment results from genetic factors, WS, or other neurological conditions are crucial for creating treatment plans and predicting outcomes.